Layer-number tailoring and template-induced orientation control of 2D perovskites on 3D perovskites by adopting the Dion–Jacobson phase. (1st November 2022) - Uzurano, Genya; Abe, Kentaro; Saito, Tomoki; Fujii, Akihiko; Ozaki, Masanori
Abstract: Orientation-controlled 2D perovskites consisting of octahedral monolayers have been realized on 3D perovskites. By bar-coating a Dion–Jacobson (DJ) phase 2D perovskite precursor solution onto 3D perovskite thin films, the conversion of the top layer of 3D perovskite to 2D perovskite was promoted, and the optimal 2D/3D heterostructure could be fabricated. The orientation of the DJ 2D perovskite could be controlled horizontally or obliquely according to the 3D perovskite template thin films; the 2D perovskite was obliquely oriented on (200)/(112)-oriented CH3 NH3 PbI3, and horizontally oriented on (110)-oriented CH3 NH3 PbI2.5 Cl0.5 . This approach would boost the stability and power conversion efficiency of 2D/3D heterostructures.